Formação de uma infraestrutura de informação para telerradiologia: uma série de estudos de caso baseados na teoria de projeto para complexidade dinâmica - Oliveira, Márcio Adamec Lopes (2015)
Technological developments have provided a variety of integrated tools that favor the emergence of information technology solutions and hence the arising of new infrastructures, although there is an increase in the complexity of these solutions. Teleradiology and local solutions for distribution of medical images are evidences of such technological developments. However, it is not known the existence of an infrastructure for teleradiology with characteristics of the so called Information Infrastructures (II), such as: capacity for dynamic organization, built by a growing and heterogeneous technical and social elements with high levels of adaptation and variation, and also holding decentralized and episodic control, that can evolve unbounded and under various conditions. Such infrastructure, if applied to local and global solutions for teleradiology, favors the emergence of a public social space for radiology practices, breaking down the boundaries between the local and the global. This work aims to understand what obstacles hinder the formation of such an information infrastructure. For this, we used the design theory for dynamic complexity (DTDC) in information infrastructure, based on the theory of complex adaptive systems (CAS), as the main reference in the investigation of a series of case studies in teleradiology. To achieve this goal, a study was conducted based on empirical descriptions of solutions for teleradiology, seeking for evidence in each case, resulting in a compiled set of knowledge qualities, shortcomings and obstacles mapped to a set of design rules of the DTDC. The result of this investigation shows the technical and social disability around the adaptability as a major factor to hinder the expansion of teleradiology and hence the formation of an information infrastructure. Finally, it was concluded that despite the growing number of solutions for teleradiology, it was not observed an II for teleradiology; and that the key to the formation of such an II is designing to enable the maximum sociotechnical flexibility, i.e., the ability to adapt continuously with high level of independence between the elements and able to deal with diverse social and technical contexts.